The Cost of Tillage - G. F. Sassenrath (Kansas Agricultural Experiment Station Research Reports, 2020)
Tillage has been a common event in farming for centuries. New information and management practices are demonstrating better ways of managing the soil to reduce erosion and improve productivity and profitability. Tillage destroys the soil structure, actually increasing the weeds and reducing the water holding capacity of the soil. Highly erodible areas of a field can lose more than 5 tons of soil per year with conventional tillage. Converting to no-till management can reduce production costs more than 30 per acre per year, saving topsoil and reducing management time in the field.
Keywords: conventional tillage; conservation tillage; crop production